Effects of Ectoine on Behavior and Candidate Genes Expression in ICV-STZ Rat Model of Sporadic Alzheimer's Disease - Niloofar Bazazzadegan; Marzieh Dehghan Shasaltaneh; Kioomars Saliminejad; Koorosh Kamali; Mehdi Banan; Reza Nazari; Gholam Hossein Riazi; Hamid Reza Khorram Khorshid (Tabriz University of Medical Sciences, 2017)
Purpose: Alzheimer's disease (AD) is pathologically defined by the presence of amyloid plaques and tangles in the brain, therefore, any drug or compound with potential effect on lowering amyloid plaques, could be noticed for AD management especially in the primary phases of the disease. Ectoine constitutes a group of small molecule chaperones (SMCs). SMCs inhibit proteins and other changeable macromolecular structures misfolding from environmental stresses. Ectoine has been reported successfully prohibit insulin amyloid formation in vitro. Methods: We selected eight genes, DAXX, NFκβ, VEGF, PSEN1, MTAP2, SYP, MAPK3 and TNFα genes which had previously showed significant differential expression in Alzheimer human brain and STZ- rat model. We considered the neuroprotective efficacy by comparing the expression of candidate genes levels in the hippocampus of rat model of Sopradic Alzheimer's disease (SAD), using qPCR in compound-treated and control groups as well as therapeutic effects at learning and memory levels by using Morris Water Maze (MWM) test. Results: Our results showed significant down-regulation of Syp, Mapk3 and Tnfα and up-regulation of Vegf in rat's hippocampus after treatment with ectoine comparing to the STZ-induced group. In MWM, there was no significant change in swimming distance and time for finding the hidden platform in treated comparing to STZ-induced group. In addition, it wasn't seen significant change in compound-treated comparing to STZ-induced and control groups in memory level. Conclusion: It seems this compound may have significant effect on expression level of some AD- related genes but not on clinical levels.